Feasibility and Accuracy of HIV Testing of Children by Caregivers Using Oral Mucosal Transudate HIV Tests. (1st June 2021) - Dziva Chikwari, Chido; Simms, Victoria; Kranzer, Katharina; Dringus, Stefanie; Chikodzore, Rudo; Sibanda, Edwin; Webb, Karen; Redzo, Nicol; Mujuru, Hilda; Apollo, Tsitsi; Ncube, Getrude; Hatzold, Karin; et al.
Abstract : Background: Children encounter multiple barriers in accessing facilities. HIV self-testing using oral mucosal transudate (OMT) tests has been shown to be effective in reaching hard-to-reach populations. We evaluated the feasibility and accuracy of caregivers conducting HIV testing using OMTs in children in Zimbabwe. Methods: We offered OMTs to caregivers (>18 years) living with HIV to test children (2–18 years) living in their households. All caregivers were provided with manufacturer instructions. In Phase 1 (January–December 2018, 9 clinics), caregivers additionally received a demonstration by a provider using a test kit and video. In Phase 2 (January–May 2019, 3 clinics), caregivers did not receive a demonstration. We collected demographic data and assessed caregiver's ability to perform the test and interpret results. Caregiver performance was assessed by direct observation and scored using a predefined checklist. Factors associated with obtaining a full score were analyzed using logistic regression. Results: Overall 400 caregivers (83.0% female, median age 38 years) who were observed tested 786 children (54.6% female, median age 8 years). For most tests, caregivers correctly collected oral fluid [87.1% without provider demonstrations (n = 629) and 96.8% with demonstrations (n = 157), P = 0.002]. The majority correctly used a timer (90.3% without demonstrations and 96.8% with demonstrations, P = 0.02). In multivariate logistic regression caregivers who obtained a full score for performance were more likely to have received a demonstration (odds ratio 4.14, 95% confidence interval: 2.01 to 8.50). Conclusions: Caregiver-provided testing using OMTs is a feasible and accurate HIV testing strategy for children. We recommend operational research to support implementation at scale. Abstract : Supplemental Digital Content is Available in the Text.